2006
DOI: 10.1016/j.cell.2006.02.037
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen Implicates miRNA-372 and miRNA-373 As Oncogenes in Testicular Germ Cell Tumors

Abstract: Endogenous small RNAs (miRNAs) regulate gene expression by mechanisms conserved across metazoans. While the number of verified human miRNAs is still expanding, only few have been functionally annotated. To perform genetic screens for novel functions of miRNAs, we developed a library of vectors expressing the majority of cloned human miRNAs and created corresponding DNA barcode arrays. In a screen for miRNAs that cooperate with oncogenes in cellular transformation, we identified miR-372 and miR-373, each permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
985
1
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,191 publications
(1,013 citation statements)
references
References 49 publications
16
985
1
11
Order By: Relevance
“…Plasmids encoding for different microRNAs and its corresponding control were obtained from the miR‐Vec library (Voorhoeve et al ., 2006). The CBX7 reporter plasmid has been described before (O'Loghlen et al ., 2012) and was used to derive the CBX7 3′UTR 9.1/2 reporter by Gibson assembly.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids encoding for different microRNAs and its corresponding control were obtained from the miR‐Vec library (Voorhoeve et al ., 2006). The CBX7 reporter plasmid has been described before (O'Loghlen et al ., 2012) and was used to derive the CBX7 3′UTR 9.1/2 reporter by Gibson assembly.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, multiple microRNAs in miR-106 family and related miRNAs rescue Ras-induced senescence and induce colony formation in soft agar in HMECs via downregulation of p21 by miR-106/302 [28]. They are associated with progression of variable tumors; miR-106a and miR-106b in gastric adenocarcinoma [29], miR-17-5p and miR-372 in squamous cell carcinoma [30], miR-372 and miR-373 in testicular germ cell tumors [10], and miR-373 with miR-520c in the metastatic tumors [31]. Moreover, inactivation of p21 and p16 INK4a facilitates immortalization and anchorage independent growth of mouse fibroblasts [11].…”
Section: Discussionmentioning
confidence: 99%
“…p21 is involved in the Ras G12V -induced senescence in different human cells; inhibition of p21 expression results in Ras G12V -resistant growth in BJ foreskin fibroblasts [10] and LF1 human lung fibroblasts [11]. Treatment of various human cells with low dose doxorubicin (200 ng/ml) also induces growth arrest with high expressions of p53 and p21 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Direct cloning strategies and bioinformatic prediction based on the presence of conserved hairpin structures and sequences have suggested that animal genomes encode hundreds, perhaps thousands, of microRNAs (Lagos-Quintana et al, 2001;Lau et al, 2001;Lee and Ambros, 2001;Lai et al, 2003;Lim et al, 2003a;Lim et al, 2003b;Kim and Nam, 2006). These small RNAs regulate early development, cell specification, differentiation, and proliferation (Lee et al, 1993;Pasquinelli et al, 2000;Reinhart et al, 2000;Ambros, 2003;Bartel, 2004;Griffiths-Jones, 2004;Hobert, 2004;Du and Zamore, 2005;Hatfield et al, 2005;Morris and McManus, 2005;O'Donnell et al, 2005;Carthew, 2006;Esquela-Kerscher and Slack, 2006;Naguibneva et al, 2006;Plasterk, 2006;Slack and Weidhaas, 2006;Voorhoeve et al, 2006).…”
Section: Introductionmentioning
confidence: 99%